2019
DOI: 10.1186/s12859-019-3271-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically characterizing individual clinical change by the steady state of disease-associated pathway

Abstract: BackgroundAlong with the development of precision medicine, individual heterogeneity is attracting more and more attentions in clinical research and application. Although the biomolecular reaction seems to be some various when different individuals suffer a same disease (e.g. virus infection), the final pathogen outcomes of individuals always can be mainly described by two categories in clinics, i.e. symptomatic and asymptomatic. Thus, it is still a great challenge to characterize the individual specific intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In the study, the authors integrate 10 different types of biological networks such as drug-disease, drug-side effects, drug-target, and seven drug-drug networks. The results concluded that deepDR predicted approved drugs such as risperidone and aripiprazole for the treatment of Alzheimer's disease (AD), whereas methylphenidate and pergolide for treatment of Parkinson's disease (PD) [ 291 ]. Likewise, Chen et al 2020 constructed an AI-based novel algorithm called as iDrug ( https://github.com/Case-esaC/iDrug ) for the integration of drug repositioning and drug-target prediction through cross-network embedding.…”
Section: Applications Of Artificial Intelligence In Drug Development mentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, the authors integrate 10 different types of biological networks such as drug-disease, drug-side effects, drug-target, and seven drug-drug networks. The results concluded that deepDR predicted approved drugs such as risperidone and aripiprazole for the treatment of Alzheimer's disease (AD), whereas methylphenidate and pergolide for treatment of Parkinson's disease (PD) [ 291 ]. Likewise, Chen et al 2020 constructed an AI-based novel algorithm called as iDrug ( https://github.com/Case-esaC/iDrug ) for the integration of drug repositioning and drug-target prediction through cross-network embedding.…”
Section: Applications Of Artificial Intelligence In Drug Development mentioning
confidence: 99%
“…Similarly, X. Zeng et al . 2019 developed a DL-based drug repurposing tool, called deepDR ( https://github.com/ChengF-Lab/deepDR ), which is used to find new repurposed drugs for AD and PD [ 291 ]. Furthermore, [ 474 ] proposed telmisartan as potential repurposed drug for AD by using a genetic network-driven classification model.…”
Section: Involvement Of Artificial Intelligence In Drug Development: mentioning
confidence: 99%
“…There are few methods that allow the pathway analysis of longitudinal data. They include Attractor analysis of Boolean network of Pathway (ABP) (Sun et al, 2019), Longitudinal Linear Combination Test (LLCT) (Khodayari Moez et al, 2019), Time-Course Gene Set Analysis (TcGSA) (Hejblum et al, 2015), and Gene Set Enrichment Analysis (GSEA) for time series (Subramanian et al 2005). ABP allows sophisticated post-processing of sample-specific pathway scores, but it has not been implemented into an R package, which hinders the ease of its usage.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used in systems biology and high-throughput techniques have successfully reconstructed various disease-related networks for pathological conditions, such as cancer, type 2 diabetes mellitus (T2DM), and influenza. These methods enable the integration and interpretation of functional genomic datasets and the identification of novel biomarkers or modules, which can aid in the elucidation of the molecular mechanisms of diseases ( Tang et al, 2018 ; Sun et al, 2019b ; Wu Y. et al, 2020 ). In particular, multilevel analysis based on tissue-related networks can systemically reveal the pathophysiology of the disease through the integration of several target tissues and the identification of key pathways or biomarkers ( Knaack et al, 2014 ; Sun et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%